Leu72Met408 Polymorphism of the Ghrelin Gene Is Associated With Early Phase of Gastric Emptying in the Patients With Functional Dyspepsia in Japan - Yamawaki, Hiroshi (J Neurogastroenterol Motil, 2015)
BACKGROUND/AIMS: There are no available data about the relationship between ghrelin gene genotypes and early phase of gastric emptying in functional dyspepsia (FD) as defined by Rome III classification. METHODS: We enrolled 74 patients presenting with typical symptoms of FD and 64 healthy volunteers. Gastric motility was evaluated using the (13)C-acetate breath test. We used Rome III criteria to evaluate upper abdominal symptoms and self-rating questionnaires for depression (SRQ-D) scores to determine status of depression. The Arg51Gln (346G>A), preproghrelin (3056T>C), Leu72Met (408C>A), Gln90Leu (3412T>A) and G-protein β3 (825C>T) polymorphisms were analyzed in the DNA from blood samples of enrolled subjects. Genotyping was performed by polymerase chain reaction. RESULTS: There was a significant relationship between the Gln90Leu3412 genotype and SRQ-D score in FD patients (P = 0.009). Area under the curve at 15 minutes (AUC(15)) value was significantly associated with the Leu72Met408 genotype (P = 0.015) but not with entire gastric emptying. CONCLUSIONS: The Leu72Met (408C>A) single nucleotide polymorphism was significantly associated with early phase of gastric emptying in FD patients. Further studies will be necessary to clarify the association between ghrelin gene single nucleotide polymorphisms and early phase of gastric emptying in FD patients.